Evaluasi Pelaksanaan Review Pengobatan Pasien COVID-19 Oleh Apoteker Berdasarkan Snars 1.1 Di Instalasi Rawat Inap Anggrek RSUP Fatmawati Jakarta Periode Juli-Agustus Tahun 2021 - Subhan, Ahmad (RSUP Fatmawati, 2023)
Fatmawati Hospital is referral hospital for COVID-19 patients that seeks to ensure safety in patient care based on SNARS 1.1. COVID-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2) This descriptive study was conducted in an observational retrospective manner to evaluate the implementation of a treatment review by pharmacists based on SNARS 1.1 for COVID-19 patients in the Orchid Room of Fatmawati Hospital for the period of July-August 2021, data collection using total sampling. Pharmacists are expected to review 4 documents including pharmacological medical instructions and monitoring of patient drug administration, information and education of inpatient integrated patients and families, provision of patient information and/education and Integrated Patient Progress Records. Implementation of medication review is said to compliant if pharmacist reviews 4 documents, less compliant if reviews 3 documents, less compliant if reviews 2 documents and is not compliant if there is only 1 document reviewed. Results evaluation showed: from 322 medical records that met the inclusion criteria 215 (66.77%). Based on gender, female patients were 56.28%, with the most length of stay was 7-14 days 43.26%, and the outcome improved was 65.58%. review of treatment by pharmacists based on SNARS 1.1 adhered to 13.03%, less compliant 20%, less compliant 34.88% and nonadherent 32.09%. The results of statistical analysis using the chi square test concluded that there was a significant relationship between the implementation of medication reviews by pharmacists and patient care outcomes with p value = 0.006 and there was no significant relationship between the implementation of medication reviews by pharmacists and the length of stay (LOS) of patients with p value. = 0.109.